Analisis Sustainability Pengrajin Purun Kecamatan Haur Gading Amuntai - Rahma Yuliani; Widyakanti Widyakanti; Adisti Rahmatiasari (At-Taradhi Jurnal Studi Ekonomi, 2021)
Craftsmen in the village of Pulantani, Kecamatan Haur Gading, Hulu Sungai Utara produces handicraft products derived from purun. The types produced are baskets, bags, mats (lampit) and hats. The product has been well produced, but there are problems related to its business continuity which still not optimal. This research examines the sustainability of purun craftsmen based on three aspects of sustainable development; environmental, economic, and social aspects. This research using a qualitative descriptive as an analysize method with primary data source and secondary data source which obtained by some interviews and observations. The research was analyzed using the theory of three sustainable pillars to look at environmental, social and economic factors. The results of the study based on analysis using the theory of three sustainable pillars then based on environmental factors proved by the absence of hazardous waste produced purun products. From the economic pillars it brings change to the economic income of the purun craftsmen community. As well as social factors, the craftsmen community, “Kelompok Usaha Berkat Ilahi” has been running for almost 2 years and will continue for the next few years. This proves that the existence of the craft purun activity can provide prosperity to the economy and the people of purun craftsmen community. Pengrajin di Desa Pulantani Kecamatan Haur Gading Kabupaten Hulu Sungai Utara memproduksi produk kerajinan turunan purun. Jenis yang diproduksi adalah bakul, tas, tikar (lampit) dan topi. Produk telah diproduksi dengan baik, tetapi permasalahan terkait berkelanjutan usahanya masih belum optimal. penelitian ini meneliti tentang keberlanjutan pengrajin purun yang dilihat berdasarkan tiga aspek pembangunan berkelanjutan yaitu aspek lingkungan, ekonomi, dan sosial. Penelitian menggunakan metode deskriptif kualitatif dengan data primer dan data sekunder, pengumpulan data dilakukan melalui observasi dan wawancara. Analisis data dalam penelitian ini menggunakan teori tiga pilar berkelanjutan untuk melihat faktor lingkungan, sosial dan ekonominya. Hasil penelitian setelah analisis menggunakan teori tiga pilar berkelanjutan maka berdasarkan faktor lingkungan terbukti dengan tidak adanya limbah berbahaya yang dihasilkan produk purun. Dari pilar ekonomi membawa perubahan kepada pendapatan ekonomi masyarakat pengrajin purun. Serta dari faktor sosial, kelompok usaha maju bersama berkat ilahi ini sudah berjalan hampir 2 tahun dan akan berlanjut hingga beberapa tahun mendatang. Hal ini membuktikan bahwasanya adanya kerajinan purun ini dapat memberikan kesejahteraan bagi perekonomian masyarakat pengrajin purun.